An effective four-step approach in treating refractory seroma after mastectomy for breast cancer - Cao, Rui; Zhang, Jing; Su, An; Bao, Haoshi; He, Zhou; Wu, Jiannan (Frontiers in Oncology, 2025)
BackgroundPostoperative chest wall seroma is a common complication following modified radical mastectomy. When persistent, it can lead to the formation of a dense fibrous capsule (pseudobursa), resulting in a refractory seroma that is unresponsive to conventional treatments and may delay essential adjuvant therapies. Surgical excision of the capsule carries significant risks. This study introduces a less invasive surgical technique to manage this challenging condition.MethodsFrom 2018 to 2021, 20 patients with refractory seroma after modified radical mastectomy were included in this retrospective study. Inclusion required seroma persistence for over one month despite repeated aspirations, with the presence of a fibrous capsule confirmed by ultrasonography. A minimally traumatic, four-step technique was employed under local anesthesia, involving capsule scraping, “cross-hatch” scoring, and flap fixation. A drainage tube was inserted post-procedure. Color Doppler ultrasound was used for pre- and post-procedural assessment.ResultsThe study included 20 female patients with a median age of 57.5 years. All patients had node-positive breast cancer. The “cross-hatch” capsular scoring technique was successfully performed in all cases. The median postoperative drainage time was 7 days (range 6–12 days). During a median follow-up of 3 months, no seroma recurrence was observed. The procedure was well-tolerated with minimal pain, and no significant complications such as hematoma or infection occurred.ConclusionThe “cross-hatch” capsular scoring technique is a safe, effective, and less invasive method for managing refractory post-mastectomy seroma. This approach minimizes patient trauma, reduces recovery time, and helps maintain the continuity of adjuvant therapies, thereby offering a valuable alternative to more aggressive surgical interventions.